THE EFFECT OF USING LETTER-FISHING MEDIA ON LETTER RECOGNITION ABILITY AND LEARNING INDEPENDENCE OF CHILDREN AT RA KEBUN ILMU - Kamalasari, Kamalasari; Sujarwo, Sujarwo (Jurnal Visi Ilmu Pendidikan, 2025)
Letter recognition is a fundamental aspect of early childhood literacy. This study aims to analyze the effects of fishing-letter media and poster media on children"™s letter recognition and learning independence. A quantitative experimental design was employed involving 51 children at RA Kebun Ilmu, divided into an experimental group (26 children) and a control group (25 children). Instruments included a letter recognition test (24 items) and a learning independence questionnaire (20 statements). Data were analyzed using the Wilcoxon Signed-Rank Test and Mann-Whitney U Test. The results indicate that fishing-letter media significantly improved letter recognition (Z = 3.746; p < 0.001) and learning independence (Z = 3.543; p < 0.001), whereas poster media did not show significant effects (p > 0.05). Furthermore, there were significant differences between the experimental and control groups (p < 0.001). Thus, fishing-letter media is more effective in enhancing early literacy and learning independence among young children.